Genuine motorische Phänomene bei schizophrenen Psychosen: Theoretischer Hintergrund und Kontextdefinition = Genuine motor phenomena in schizophrenic psychoses : theoretical background and definition of context - Hirjak, Dusan; Thomann, Philipp; Kubera, Katharina Maria; Wolf, Robert Christian (Der Nervenarzt, 2018)
Besides positive and negative symptoms, motor abnormalities have been increasingly recognized as central symptoms of schizophrenia. Recent investigations of antipsychotic-naive first-episode patients with schizophrenia found significantly higher rates of genuine motor abnormalities (GMA) when compared to healthy individuals. The first part of this article introduces the historical and clinical background of GMA in schizophrenia. In the second part the relevance of scientific research and clinical implication of GMA in schizophrenia are discussed. Finally, this article aims at presenting a conceptual framework and a reference system involving both genuine and drug-induced motor abnormalities. The future clinical implications of GMA research are presented and multimodal and transdiagnostic studies are advocated. Future research on GMA will not only essentially enrich the formation of psychiatric theories but also promote progress in clinical neuroscience.
Gesehen am 04.09.2019
Online publiziert:7. Juli 2017